Efektivitas Edukasi Berbasis Media PowerPoint dalam Pencegahan Penyalahgunaan Dextromethorphan pada Remaja di SMK Negeri 4 Bengkulu Selatan - Fiiska Nur Safitri; Oky Hermansyah; Marisadonna Asteri; Dwi Kurnia Putri; Rezqa Hasanah (Yayasan Literasi Sains Indonesia, 2026)
The misuse of dextromethorphan among adolescents and young adults has become a health issue that is increasingly receiving global attention. Drug abuse remains a public health problem that requires serious attention in Indonesia. This issue not only involves the misuse of narcotic and psychotropic drugs, but has also expanded to include over-the-counter limited drugs that are easily obtained without a prescription, such as dextromethorphan. Adolescents are the group most vulnerable to drug abuse behavior. Several factors contribute to this problem, including peer influence, lack of knowledge about drugs and their effects, and the ease of obtaining limited over-the-counter medicines. In Bengkulu Province, the Indonesian Food and Drug Authority and Bengkulu Regional Police in 2023 confiscated thousands of bottles of cough medicines such as Samcodin and Komix that were proven to be misused by teenagers, including in South Bengkulu. This study used the accidental sampling method with a single variable. Data were collected through questionnaires before and after educational intervention involving 39 respondents to determine students' level of knowledge about the dangers of dextromethorphan abuse. The results showed that before the educational intervention, 11 respondents had good knowledge, 5 had moderate knowledge, and 23 had poor knowledge. After the intervention, all respondents (39 people or 100%) were categorized as having good knowledge. The Wilcoxon test result showed a p-value of 0.000 (p < 0.05), indicating that the educational intervention significantly improved adolescents' knowledge about the dangers of dextromethorphan abuse.